Sistem Informasi Persediaan Oli Dengan Metode ROP di CV. Sumber Lumas Semarang - Suwardi Suwardi; Danang Danang (UNIVERSITAS STEKOM, 2019)
Inventory is one component of company assets which is very important in supporting the continuity of operational activities of trading companies. The process of inventory mutation, makes business owners required to be able to provide accurate and relevant information about inventory. This information can be generated from the use of a merchandise inventory information system which can help business owners to know the processes related to the availability of these merchandises. To monitor the process of oil transfer and oil availability on the CV. Sumber Lumas Semarang, business owners still use manual data input by using Microsoft Excel applications and hand-written stock cards. The manual use of this system causes several obstacles, including: frequent occurrences of oil inventory balances due to human error factors in recording items on stock cards, over-stock/stock out of oil inventory in warehouses and late oil inventory reporting due to data from stock cards moved into the Microsoft Excel format every month that requires precision and a lot of time. This makes the oil inventory report is not up to date. Observed at the problems faced today, CV. Sumber Lumas Semarang needs a system which can overcome the problems of merchandise inventory record and can produce relevant and accurate merchandise inventory information.